Transient Exacerbation of Nasal Symptoms following Endoscopic Transsphenoidal Surgery for Pituitary Tumors: A Prospective Study - Davies, Benjamin M.; Tirr, Erica; Wang, Yi Yuen; Gnanalingham, Kanna K. (Journal of Neurological Surgery Part B: Skull Base, 2017)
Object Endoscopic transsphenoidal surgery is the commonest approach to pituitary tumors. One disadvantage of this approach is the development of early postoperative nasal symptoms. Our aim was to clarify the peak onset of these symptoms and their temporal evolution.Methods The General Nasal Patient Inventory (GNPI) was administered to 56 patients undergoing endoscopic transsphenoidal surgery for pituitary tumors preoperatively and at 1 day, 3 days, 2 weeks, 3 months, and 6 to 12 months postoperatively. Most patients underwent surgery for pituitary adenomas (N = 49; 88%) and through a uninostril approach (N = 55; 98%). Total GNPI (0–135) and scores for the 45 individual components were compared.Results GNPI scores peaked at 1 to 3 days postoperatively, with rapid reduction to baseline by 2 weeks and below baseline by 6 to 12 months postsurgery (p < 0.01). Of the 45 individual symptoms on the GNPI scale, 19 (42%) worsened transiently after surgery (p < 0.05). Functioning tumors had a higher GNPI scores at postoperative day 1 and 3 than nonfunctioning tumors, although their temporal evolution was the same (p < 0.05).Conclusions Nasal morbidity following endoscopic transsphenoidal pituitary surgery is common, but transient, more so in the functioning subgroup. Nasal symptoms improve below baseline by 6 to 12 months, without the need for specific long-term postoperative interventions in the vast majority of patients.
Keywords: endoscopic; transsphenoidal; pituitary tumor; adenoma; nasal symptoms; GNPI